Classificação das hipersuperfícies paralelas e semi-paralelas em S^nxR - Tassi, Marcos Paulo (Universidade Federal de São Carlos, 2015)
The aim of this Masters dissertation is to show a classication of parallel and semi-parallel hypersurfaces of Sn _ R, based on the work of Joeri Van der Veken and Luc Vrancken, in [12]. The classification that we will present is a generalization of the classification of parallel hypersurfaces in Rn and Sn given by H.B. Lawson (see [8]), the classification of semi-parallel hypersurfaces obtained by J. Deprez for the euclidean space (see [5]) and by F. Dillen for the case of space forms of positive sectional curvature (see [6]).
Keywords: Matemática; Hipersuperfícies; CIENCIAS EXATAS E DA TERRA::MATEMATICA